Effect of Relining Method on Dimensional Accuracy of Posterior Palatal Seal. An In Vitro Study - Yeongjeong Kim, DDS, DMD,1 Konstantinos X. Michalakis, DDS, PhD, FACP,2 (Journal of Prosthodontics, 2008)
The posterior palatal seal contributes to the retention of the complete denture. Distortion of this area can occur during reline procedures